Effects of polypeptide-k supplemented soft bun on blood glucose level in healthy adults. - Yong, Yean Sirn; Lee, Cheng Lok; Ahmad, Zuraini; Yaacob, Azhar; Abdullah, Muhammad Nazrul Hakim (Academic Journals, 2011)
The alm ol thls study llr to ovaluate lho offocts of Polypoptlde-k (Ppk) suppl€montod sofl roll on lhs blood glucose levelof 18 haalthy Indlvldu.l..s comprred to control sott roll alone. Healthy Indlvlduals were fasted ovornlght lnd blood was taken at basellns (0 mlh) befors cohsumptlon of conlrol soft roll, and at 0, 30, 90, 150 and 210 mln. Glucoso lovsl was thsn dstehlhgd. Thl6 proo€duro waa ropoatod wlth Ppk strpplemanled 6oft rcll on th€ same Indlvldual3 the next d.y. Ppk supplomonlod roll .oll showod slghlllcant docrotnghl (p<0.05) In glucoso level wh.n compa.ad to conhol sofl roll al 90, 150 and 210 mln, Blood glucose lev6l wlth Ppk supplem6nted sotl roll roqulros slallstlcally slgnlllcant lessor llme, 110 mh, to drop to basellne glucoss levol oa compared to control goft roll, r{hlch lequllos 190 mln, Blood glucose levol wlth Ppft supplemented sott roll turthsr dropped to .0.9 mmol/L atler 210 mln whlle for control aotl roll, blood glucose level ohly droppod sllghtly io "0.2 mmol/l. In concluslon, Ppk supplemented soll roll caused ohhanced rcducllon In blood glucoso l6vol as comp..od to control soft roll In healthy adult6.